Activity of benomyl for control of postbloom fruit drop of citrus caused by Colletotrichum acutatum - Peres, N. A. R. [UNESP]; Souza, N. L. [UNESP]; Zitko, S. E.; Timmer, L. W. (Scientific Societies, 2002)
Postbloom fruit drop (PFD) of citrus caused by Colletotrichum acutatum produces orange-brown lesions on petals and induces the abscission of young fruitlets and the retention of the calyces. Despite the fact that C. acutatum is not highly sensitive to benomyl in culture, this fungicide provides good control of the disease under field conditions. This study was undertaken to determine the effect of benomyl on various stages of disease development to understand the basis for its effectiveness in the field. We found that benomyl at 1.0 μg/ml reduced colony area of C. acutatum by about 75% and completely inhibited growth of C. gloeosporioides. Benomyl did not prevent conidial germination even at 100 μg/ml, but reduced germ tube elongation at 10 and 100 μg/ml. When benomyl was applied to flower clusters on screen-house-grown plants before inoculation, disease severity was greatly reduced. Applications at 24 and 48 h, but not at 72 h, after inoculation reduced PFD severity. Application of benomyl to symptomatic petals not bearing conidia did not prevent or reduce production of inoculum. Application to petals bearing conidia reduced viability of these fungal propagules by only about 50%. The viability of appressoria on mature leaves was not affected by benomyl application. Even when appressoria on mature leaves were stimulated to germinate by treatment with flower extracts, subsequent application of benomyl did not reduce propagule numbers below original levels. Benomyl appears to act by preventing infection and early development of the fungus in petals. However, once symptoms have developed, this fungicide has only minimal effects on further disease development and spread.
Keywords: Disease control; Fungi; Fungicides; Flower extracts; Fruits; Citrus; Colletotrichum; Glomerella acutata; Glomerella cingulata